Treatment of relapsed or refractory Hodgkin’s lymphoma with lenalidomide combined with PD-1 monoclonal antibody: a case report and literature review - Dong, Hongjuan; Wang, Rui; Cheng, Lu; Ma, Shirong; Zhu, Li; Zhao, Jing; Gao, Guangxun (Frontiers in Oncology, 2025)
The current standard treatment for relapsed or refractory Hodgkin’s lymphoma involves salvage chemotherapy followed by high-dose chemotherapy and sequential autologous stem cell transplantation. However, for patients who cannot tolerate intense chemotherapy or do not meet the conditions for autologous stem cell transplantation, there is a need to explore new treatment options. We report a case of an elderly patient with multiple relapses of classical Hodgkin’s lymphoma who experienced repeated disease progression despite undergoing multiple lines of treatment including novel agents such as CD30 monoclonal antibody and PD-1 monoclonal antibody. The patient finally achieved sustained remission after receiving a combination therapy of lenalidomide and PD-1 monoclonal antibody. We hope to provide hematologists with a candidate treatment option for patients with relapsed or refractory Hodgkin’s lymphoma through this case report.